Relationship of Queue System with Patient Satisfaction at X Bojonegoro Hospital Obstetrician Clinic - Wilujeng Puspitasari; Suratmi Suratmi; Nurul Hikmatul Qowi (Surya : Jurnal Media Komunikasi Ilmu Kesehatan, 2022)
Background: Service is a very important thing that must be considered by a hospital. Good service provided will affect the level of patient satisfaction Ease of access in the service is very expected by every patient, but what happens is a queuing system that makes patients go through many procedures so that it will take a long time and will cause patient dissatisfaction with hospital services.Objectives: The purpose of this study was to find out the relationship between the Queuing System and Patient Satisfaction.Design: The study used a correlational analytic design with a crossectional approach, with consecutive sampling techniques obtained by 90 patients. The independent variable is the queuing system and the dependent variable is Patient Satisfaction. The instrument used for both variables is a closed questionnaire.Results: The results showed that of the 90 respondents who stated that almost all patients rated the Aisyiyah hospital queue system as good as 72 patients (80%), most patients were satisfied with Aisyiyah hospital services, which was as many as 60 patients (66.7%). Spearmen Rank test results known p-value = 0.012 means p < 0.05. There is a relationship between the Queue System and Patient Satisfaction.Conclusions: Based on the results of the study, it is expected that the hospital will provide the best service especially in terms of the queuing system such as providing fast and appropriate services so that patients do not wait too long so that patient satisfaction can be achieved